EKSISTENSI CONTENT CREATOR TIKTOK BERDASARKAN PERILAKU SOSIAL MAHASISWI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS UDAYANA - Herdiansyah, Naufal Rafa; Arjawa, I Gusti Putu Bagus Suka; Aditya, I Gusti Ngurah Agung Krisna (Triwikrama: Jurnal Ilmu Sosial, 2025)
This research aims to analyze the existence of TikTok creator content based on the social behavior of students at the Faculty of Social and Political Sciences, Udayana University. The research method used is a qualitative approach with a descriptive - explanatory type and is dissected by learning theory with the social behavior paradigm of B.F. Skinner. This research describes the activities of female students using the TikTok application and female students as content creators. The activity of accessing social media, especially TikTok, has become very popular among female students because the activities carried out only rely on playing social media. A number of students from the Faculty of Social and Political Sciences admit that spending time on social media, especially TikTok, can take up 6 to 7 hours a day. Then, female students as content creators admitted that this application can be easily watched by many people if we follow what is currently popular at that time, such as dance shows, daily shows and can use background sound which is also widely used by other users at that time.